FINANCIAL CAPABILITY STUDY OF MICRO, SMALL AND MEDIUM ENTERPRISES OWNER WITH SUPERIOR PRODUCT IN MADIUN REGENCY - Agnisa Sahrul Riffianto; Tatik Suryani (STIE Perbanas Surabaya, 2016)
Financial Capability is become the main topic in this study. The firts aim of this study is to analyze and measure financial capability of MSME (Micro, Small and Medium Enterprises) owner with superior products. The subjects of this study are MSME owner in Madiun Regency, East Java, Indonesia. Financial Capabilty measure by Funding Decision, Proft Sharing, Investment Decision and Financial Performance. By using triangulation method, this study found that Fincancial Capability of the MSME owner still on low level. MSME's funding decision is limited and not supported by third party like Bank. MSME's profit sharing is good for MSME's development. But their perception about business development is not right. MSME's Investment decision perception about land investment is wrong.